The Effect of Servant Leadership on the Work Productivity of PT. Fastrata Buana Bekasi - Anita Novialumi (Peneliti.net, 2021)
This research is an exploratory research type with quantitative insights. This study aims to determine the effect of Servant Leadership on the labor productivity of PT. Fastrata Buana Bekasi. The data used is primary data and general data. The number of respondents in this research consisted of 30 employees with a total sampling technique. The analysis in this study includes descriptive analysis and path analysis using SPSS version 25. The method of analysis used is the Analysis of the Relevance Line Selection. Based on the results of the analysis of regress, the leadership that was entrusted to the employees of PT. Fastrata Buana Bekasi, many offices have a positive and significant impact on labor productivity